Using the Theoretical Framework of Acceptability for qualitative assessment of the "COMBAT" VAW intervention in Ghana - Ruby Hornuvo; Adolphina Addo-Lartey; Deda Ogum Alangea; Phyllis Dako-Gyeke (Public Library of Science (PLoS), 2022)
Violence against women (VAW) is a global health problem, which leads to negative sexual, reproductive, mental and physical health outcomes, as well as death in extreme cases. Globally, over 35% of women are reported to have experienced some form of violence, while in Ghana, 37% of women have ever experienced physical violence. Considering that the sustainability of community-based VAW interventions is largely dependent on ownership, this study used the Theoretical Framework of Acceptability (TFA) to assess the COMBAT (Community Based Action Teams) intervention (for example, ethicality, self-efficacy, and intervention coherence) which was implemented to prevent violence against women in Ghana. This qualitative research study was conducted at baseline and end-line of the intervention, which used COMBAT as a vehicle to change social norms on gender and violence in the Central region, Ghana. Participants comprised of adult (women and men) who reside in the Agona District. We analyzed the transcripts from eight (8) Focus Group Discussions conducted within one of the two intervention recipient sites (4 female community FGDs and 4 male community FGDs). Data was analyzed thematically using the Nvivo software version 12. Through the application of the TFA, the findings show that community members perceive VAW as inappropriate at the individual and community levels (ethicality), have good knowledge of the COMBAT intervention and how it works (intervention coherence). Also, the study shows that participants have a positive attitude towards the intervention and its components (positive affective attitude), and could take up components of the intervention, by reporting and seeking for VAW support (positive self-efficacy). There was a perceived reduction in VAW practices in the various communities, as well as a reduction in the abuse of women, thereby improving their well-being (intervention effectiveness). The COMBAT strategy was accepted by the community members hence could be sustained as a culturally appropriate intervention for preventing VAW.